Establishment and application of multiplex real-time PCR for simultaneous detection of four viruses associated with porcine reproductive failure - Chen, Yuan; Luo, Shile; Tan, Jianmei; Zhang, Luhua; Qiu, Shengwu; Hao, Zhiyou; Wang, Naidong; Deng, Zhibang; Wang, Aibing; Yang, Qing; Yang, Yi; Wang, Changjian; et al. (Frontiers in Microbiology, 2023)
Many pathogens cause reproductive failure in sows suffering a broad spectrum of sequelae, including abortions, stillbirth, mummification, embryonic death, and infertility. Although various detection methods, such as polymerase chain reaction (PCR) and real-time PCR, have been widely used for molecular diagnosis, mainly for a single pathogen. In this study, we developed a multiplex real-time PCR method for the simultaneous detection of porcine circovirus type 2 (PCV2), porcine circovirus type 3 (PCV3), porcine parvovirus (PPV) and pseudorabies virus (PRV) associated with porcine reproductive failure. The R2 values for the standard curve of multiplex real-time PCR of PCV2, PCV3, PPV and PRV reached to 0.996 ,0.997, 0.996 and 0.998, respectively. Importantly, the limit of detection (LoD) of PCV2, PCV3, PPV and PRV, were 1, 10, 10, 10 copies/reaction, respectively. Meanwhile, specificity test results indicated that multiplex real-time PCR for simultaneous detection is specific for these four target pathogens and does not react with other pathogens, such as classical swine fever virus (CSFV), porcine reproductive and respiratory syndrome virus (PRRSV) and porcine epidemic diarrhea virus (PEDV). Besides, this method had good repeatability with coefficients of variation of intra- and inter-assay less than 2%. Finally, this approach was further evaluated by 315 clinical samples for its practicality in the field. The positive rates of PCV2, PCV3, PPV and PRV were 66.67% (210/315), 8.57% (27/315), 8.89% (28/315) and 4.13% (13/315), respectively. The overall co-infection rates of two or more pathogens were 13.65% (43/315). Therefore, this multiplex real-time PCR provides an accurate and sensitive method for the identification of those four underlying DNA viruses among potential pathogenic agents, allowing it to be applied in diagnostics, surveillance, and epidemiology.